Research regarding use of pneumatic linear actuator - Duțu, I.C; Axinte, T; Maican, E; Frățilă, C; Nutu, C.; Savastre, A (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
This article represents research regarding use of pneumatic linear actuator. A pneumatic linear drive is a device that creates motion in a straight line. The linear drive with solenoid in this manuscript is a pneumatic actuator. The pneumatic linear drive works only with compressed air. Compressed air usually has a pressure of between 2·105 Pa and 6·105 Pa. Linear drive with solenoid can be used for various applications, including pulling/pushing, pick-and-place applications or lifting/moving. After Introduction, the authors study two pneumatic circuits using linear drive with solenoid coupling. In fact, the first pneumatic scheme in this paper has only one device (linear drive 1-1). But, the second pneumatic circuit has two actuators (linear drives 2-1 and 2-2). Further on, the authors present two electro-pneumatic circuits. In any case, a simple electro-pneumatic circuit that has a linear drive with solenoid coupling. Moreover, the second electro-pneumatic system has a linear drive with solenoid coupling and PLC (Programmable Logic Controller). The pneumatic and electro-pneumatic circuits given in this manuscript are made using FluidSim software from Festo.